A Study of Educational Technology in the Inclusion of Special Educational Needs: विशेष शैक्षिक आवश्यकताओं के समावेशन में शैक्षिक प्रौद्योगिकी का अध्ययन - Mishra, Awnish Kumar; Tiwari, Satya Prakash (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Digital inclusion in special education is vital for ensuring equal access to education for students with Special Educational Needs (SEN). This article explores the transformative role of emerging tools, apps, and technological innovations in promoting digital inclusion in special education. It examines how assistive technologies such as screen readers, Augmentative and Alternative Communication (AAC) devices, and AI-powered adaptive learning platforms address barriers related to communication, literacy, and sensory impairments. The study highlights inclusive Learning Management Systems (LMS) and game-based tools that enhance engagement and personalized learning for SEN students. Additionally, it analyzes government policies such as India’s NEP 2020 and global initiatives by UNESCO and WHO that support accessible digital content and teacher training. Despite progress, challenges like the digital divide, high cost of assistive technologies, and resistance to adoption persist. By synthesizing evidence from peer-reviewed studies and policy documents, the paper underscores the potential of technology in bridging educational disparities and emphasizes the need for robust infrastructure and training to achieve equity. The conclusions aim to guide educators, policymakers, and technologists in creating inclusive digital learning environments for all students. Abstract in Hindi Language: विशेष शिक्षा में डिजिटल समावेशन विशेष शैक्षिक आवश्यकताओं (SEN) वाले छात्रों के लिए समान शिक्षा तक पहुँच सुनिश्चित करने में महत्वपूर्ण है। यह लेख विशेष शिक्षा में डिजिटल समावेशन को बढ़ावा देने में उभरते उपकरणों, ऐप्स और तकनीकी नवाचारों की परिवर्तनकारी भूमिका की खोज करता है। यह जांच करता है कि स्क्रीन रीडर, संवर्धित और वैकल्पिक संचार (AAC) उपकरण, और AI-संचालित अनुकूली शिक्षण मंच जैसे सहायक प्रौद्योगिकियाँ संचार, साक्षरता और संवेदी कमियों से संबंधित बाधाओं को कैसे संबोधित करती हैं। अध्ययन समावेशी शिक्षण प्रबंधन प्रणालियों (LMS) और गेम आधारित उपकरणों पर प्रकाश डालता है जो SEN छात्रों के लिए जुड़ाव और व्यक्तिगत शिक्षण को बढ़ाते हैं। इसके अतिरिक्त, यह भारत की NEP 2020 और UNESCO तथा WHO की वैश्विक पहलों सहित सरकारी नीतियों का विश्लेषण करता है, जो सुलभ डिजिटल सामग्री और शिक्षक प्रशिक्षण को बढ़ावा देती हैं। प्रगति के बावजूद, डिजिटल विभाजन, सहायक प्रौद्योगिकियों की उच्च लागत, और अपनाने में प्रतिरोध जैसी चुनौतियाँ बनी रहती हैं। सहकर्मी-समीक्षित अध्ययनों और नीति दस्तावेजों से साक्ष्य संश्लेषित करके, यह लेख शैक्षिक असमानताओं को पाटने में प्रौद्योगिकी की संभावनाओं को रेखांकित करता है, साथ ही समानता प्राप्त करने के लिए मजबूत बुनियादी ढांचे और प्रशिक्षण की आवश्यकता पर बल देता है। निष्कर्ष शिक्षकों, नीति निर्माताओं और प्रौद्योगिकीविदों को सभी छात्रों के लिए समावेशी डिजिटल शिक्षण वातावरण बनाने में मार्गदर्शन करने का लक्ष्य रखते हैं। Keywords: डिजिटल समावेशन, विशेष शिक्षा, सहायक प्रौद्योगिकी, समावेशी LMS, शैक्षिक समानता